GAMIFICATION APPROACHES IN ELT: IMPLEMENTATION AND ITS INFLUENCE ON ESP ACCOUNTING STUDENTS' VOCABULARY MASTERY - Prasongko, Angga; Farikha, Ninik; Lestari, Pritantina Yuni; Hamida, Ulfi Dina (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
High motivation and interest in the teaching and learning process are important factors in achieving learning objectives. Lecturers in the classroom have a very important role in achieving these objectives. Lecturers must use a creative, innovative, and modern learning approach in order to achieve learning objectives. Research with the aim of providing a breakthrough as a role model for technology-based English teaching and learning activities in the context of English for Specific Purpose (ESP) needs to be applied to answer these problems. This research is a qualitative type with a descriptive approach supported by quantitative data through a quasi-experimental design. The research subjects implemented by the Word-wall game in learning were carried out by lecturers through five stages. The use of the Word-wall game in learning activities significantly increased students' English vocabulary scores. The results of the study showed that the Word-wall game is an effective and interesting learning media to improve students' English vocabulary mastery and has an effect on increasing student motivation and participation in class to learning process.